E-service quality, e-trust, and e-wom toward repurchase intention: The mediating role of e-customer satisfaction among tiktok shop users in Semarang - Nafisah, Inggi; Istanti, Fredianaika (International Journal of Applied Finance and Business Studies, 2025)
The rapid expansion of e-commerce in Indonesia has been marked by the emergence of TikTok Shop, a platform that combines entertainment and commerce, particularly attracting Generation Z users. This study aims to analyze the influence of e-service quality, e-trust, and electronic word of mouth (e-WOM) on repurchase intention, with e-customer satisfaction as a mediating variable. A quantitative method was applied, involving 100 respondents selected through purposive sampling. Data were analyzed using Structural Equation Modeling with SmartPLS 4.0. The results show that e-customer satisfaction does not significantly affect repurchase intention (t = 1.907; p = 0.057), and it does not mediate the relationship between the exogenous variables and repurchase intention. E-service quality and e-trust also show no significant effect on e-customer satisfaction or repurchase intention (p > 0.05). However, e-WOM has a positive and significant influence on e-customer satisfaction (t = 2.887; p = 0.004). These findings indicate that Gen Z purchasing behavior on social commerce platforms tends to be influenced more by peer communication and digital trends rather than by traditional service quality and trust factors. This study enriches the theoretical discourse on digital consumer behavior in Indonesia and provides practical recommendations for e-commerce platforms to enhance repurchase intention strategies through social engagement, influencer collaboration, and optimized e-WOM mechanisms.